PERAN BUPATI TERHADAP PERLINDUNGAN, PENGELOLAAN, PELESTARIAN DAN PENGEMBANGAN HASIL PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN - Mahmud Rifa'i (Pemerintah Kabupaten Madiun, 2022)
The new paradigm of development is to prioritize the active or participatory role of the community and local institutions in accelerating poverty reduction and improving community welfare and employment opportunities for the community. The purpose of the research is the role of the Regent in the study of the protection, management, preservation, and development of the results of the implementation of the national program for empowering independent rural communities in terms of philosophical, sociological, and juridical aspects. The research method uses normative juridical methods, literature review and FGD. The results of the study indicate that from the physiological, sociological, and juridical aspects, the role of the Regent in protecting, managing, preserving, and developing the results of the implementation of the national program for empowering independent rural communities is crucial. The philosophical, sociological, and juridical aspects show a solid basis to the role of the Regent in the form of local government regulations with a clear scope, direction and scope.Keywords: development, participatory, preservation, protection.